Antenatal Care Initiation Among Pregnant Women in the United Arab Emirates: The Mutaba'ah Study - Nasloon Ali; Iffat Elbarazi; Iffat Elbarazi; Souha Alabboud; Fatima Al-Maskari; Fatima Al-Maskari; Tom Loney; Luai A. Ahmed (Frontiers Media S.A., 2020)
Introduction: Antenatal care (ANC) provides monitoring and regular follow-up of maternal and fetal health during pregnancy. Women with appropriate ANC tend to have better delivery and birth outcomes. This study describes the patterns of ANC utilization and factors associated with appropriate ANC initiation in the United Arab Emirates (UAE) for the first time.Methods: Baseline cross-sectional data from pregnant women who participated in the Mutaba'ah-Mother and Child Health Study between May 2017 and January 2019 was analyzed. Participants were recruited during ANC visits and completed a self-administered questionnaire that collected socio-demographic and pregnancy-related information and assessed whether it was their first ANC appointment. Regression models assessed the relationship between socio-demographic and pregnancy-related variables and "appropriate" (≤ 4 months' gestation) vs. "late" ANC initiation (>4 months' gestation).Results: At recruitment, 841 participants reported that it was their first ANC visit and half (50.2%) of these women were late initiating their ANC. Mothers who were more educated, had previous infertility treatment or previous miscarriages were all more likely to achieve appropriate ANC initiation [adjusted odds ratio (aOR): 1.66, 95% confidence interval (CI): 1.05-2.62; aOR: 3.68, 95% CI: 1.50-9.04; aOR: 1.80, 95% CI: 1.16-2.79, respectively]. Women worrying about childbirth were less likely to achieve appropriate ANC initiation (aOR: 0.54, 95% CI: 0.34-0.85).Conclusion: Half of pregnant women in this study did not achieve the global consensus guidelines on appropriate ANC initiation. Interventions among less educated women and those with previous pregnancy complications and childbirth anxiety are recommended to ensure appropriate ANC initiation.